2011
DOI: 10.1002/pbc.23284
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nephroblastoma in Africa: Results of the first French African pediatric oncology group (GFAOP) study

Abstract: BackgroundThe multidisciplinary management of nephroblastoma has been defined through multicentric prospective studies and an average 90% of patients cured expected. In Africa, such studies are uncommon and results are fragmentary or unknown in most of the countries. We report the results of the GFAOPNEPHRO 01 study using SIOP 2001 protocol approach.ProcedureFrom April 1, 2001 to March 31, 2004, 8 African Pilot Units were selected to participate in a nonrandomized prospective study. All patients referred with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…[3, 16] It is clear that proper support and infrastructure results in markedly improved outcomes for patients with WT in Africa. In Casablanca, Morocco, authors reported a 5-year OS of 79% from WT by following SIOP-9 treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…[3, 16] It is clear that proper support and infrastructure results in markedly improved outcomes for patients with WT in Africa. In Casablanca, Morocco, authors reported a 5-year OS of 79% from WT by following SIOP-9 treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Typical presentation of a child with Wilms tumour in a low income setting is a malnourished child of about 3 years with a large abdominal or flank mass, who is relatively well without acute pain or severe general malaise, but with haematuria and hypertension [3,4].…”
Section: Diagnosis and Differential Diagnosis: Diagnostic Facilities;mentioning
confidence: 99%
“…Survival in low income countries is much lower than in high income countries with reported survival in low income settings in sub-Saharan Africa ranging from 11% to 50% [3][4][5][6][7]. Known challenges are late presentation with advanced disease, malnutrition, failure to complete treatment and poorer facilities both for the specific cancer treatment and also for supportive care [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In contrast, survival rates in African settings are generally less than 45%, although one recent collaborative effort achieved an event-free survival rate of 77%. 3-8 This outcome disparity reflects lack of access to high-quality, multidisciplinary oncologic care, with many cancer facilities often situated in urban centers and within the private sector. 9-12 …”
Section: Introductionmentioning
confidence: 99%